Analisis Tindak Tutur Lokusi, Ilokusi dan Perlokusi pada Whatsapp Group Sivitas Akademika IBN Tegal - Pindha Kaptiningrum (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
Analyzing the speech act is interesting to investigate the utterance in the Islamic College, Institut Agama Islam Bakti Negara (IBN) Tegal. Generally, the research is about Islamic and education here. Then, this speech act analysis enriches the research in IBN Tegal. This study aims to analyze the utterance according to the types of speech acts performed by civitas academica of IBN Tegal and described the function of utterances. The object of this study is civitas academica of IBN Tegal. This study is qualitative descriptive research. The result of this research shown that the performed utterances could be classified into locutionary act, illocunionary act, literal speech act, nonliteral speech act, direct speech act, and indirect speech act. The performed utterances’ functions are stating, suggesting, boasting, complaining, claiming, etc.